ANALISIS PENERIMAAN KOMPUTER MIKRO DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA KANTOR AKUNTAN PUBLIK (KAP) DI JAWA TENGAH - Dewayanto, Totok (JURNAL STIE SEMARANG, 2011)
The purpose of this study was to test the level of acceptance of micro computers by auditors at accounting firms in Central Java, The current auditors in accounting firms has many uses of micro computer that can be facilitate their work. The model that used to explain acceptance of micro computer is Technology Acceptance Model (TAM) with four main construct, namely perceived usefulness, perceived ease of use, attitude toward using and user acceptance.   The result were as follows: (1) Perceived ease of use significantly influence on perceived usefulness; (2) Perceived usefulness significantly influence on attitude toward using; (3) Perceived ease of use significantly influence on attitude toward using; (4) Perceived usefulness significantly influence on user acceptance; (5) Attitude toward using did not significantly influence on user acceptance.